Soluções locais para uma equação hiperbólica - Jesus, Rafael Oliveira de (2017)
This work we will study the existence and uniqueness of the solution to the following nonlinear hyperbolic problem: where is a bounded open set of Rn with boundary - consisted of two parts -0 and -1, with -0 \ -1 = ; > 1 is a real constant and h : -1 R -! R is a continuous function and strongly monotonous in the second variable. The existence of the above problem will be done using the Faedo-Galerkin method with a special basis for V \H2( ), Strauss' approximations of continuous functions and trace theorems for non-smooth functions. The uniqueness will be obtained in the case where h = p, where 2 W1;1(-1), and p : R -! R is a Lipschitzian function and strongly monotonous.